One‐Pot Bioconversion of l‐Arabinose to l‐Ribulose in an Enzymatic Cascade - Chuaboon, Litavadee; Wongnate, Thanyaporn; Punthong, Pangrum; Kiattisewee, Cholpisit; Lawan, Narin; Hsu, Chia‐Yi; Lin, Chun‐Hung; Bornscheuer, Uwe T.; Chaiyen, Pimchai (Angewandte Chemie, 2019)
This work reports the one‐pot enzymatic cascade that completely converts l‐arabinose to l‐ribulose using four reactions catalyzed by pyranose 2‐oxidase (P2O), xylose reductase, formate dehydrogenase, and catalase. As wild‐type P2O is specific for the oxidation of six‐carbon sugars, a pool of P2O variants was generated based on rational design to change the specificity of the enzyme towards the oxidation of l‐arabinose at the C2‐position. The variant T169G was identified as the best candidate, and this had an approximately 40‐fold higher rate constant for the flavin reduction (sugar oxidation) step, as compared to the wild‐type enzyme. Computational calculations using quantum mechanics/molecular mechanics (QM/MM) molecular dynamics (MD) showed that this improvement is due to a decrease in the steric effects at the axial C4‐OH of l‐arabinose, which allows a reduction in the distance between the C2‐H and flavin N5, facilitating hydride transfer and enabling flavin reduction. Süßer Eintopf: Ein neues Konzept für die Synthese von l‐Ribulose aus l‐Arabinose beruht auf einer Eintopf‐Biokonversion mithilfe einer optimierten Pyranose‐2‐Oxidase, Xylose‐Reduktase, Formiat‐Dehydrogenase und Katalase. Laut Kinetikmessungen und MD‐Simulationen befindet sich das Zuckersubstrat in der künstlichen Pyranose‐2‐Oxidase näher an der FAD‐N5‐Position als im Wildtyp.